Effect of Dosages and Temperatures on Simalungun Red Ginger (Zingiber officinale var. Rubrum) Ethanol Extract Dipping on Masculinization of Zebra Fish (Danio rerio) as a Model Fish - Eka Fitria Febriani; Maheno Sri Widodo; Abdul Rahem Faqih (Jurnal Ilmiah Perikanan dan Kelautan, 2023)
Highlight Research Successive administration of Ginger ethanol extract to male individuals was shown to be able to produce a significant increase in sperm count, motility, viability and morphology Ethanol extract of ginger has androgenic activity which is proven to be able to increase the concentration of testosterone in serum, which functions to control the process of spermatogenesis, maintain Sertoli cells and play a role in determining the quality of spermatozoa in male organisms Giving ginger ethanol extract for 30 consecutive days to male individuals showed significant results so that ginger extract was thought to have the potential to improve male characteristics Ginger extract is potentially useful in improving healthy sperm characteristics and management of male infertility especially in those with low sperm counts   Abstract Ornamental fish are known to be easily cultivated in aquarium or pond. Many people prefer male (MF) over female fish (FF) due to their aesthetic value and productivity which lead to better pricing. The aim of this study was to determine the effect of Simalungun Red Ginger (Zingiber officinale var. Rubrum) (SRG) on masculinization. This study used dipping method which was carried out using Simalungun Red Ginger (Zingiber officinale var. Rubrum) (SRG). The temperature treatments used in this study were 28°C and 32°C. For this research, an experimental study with a Completely Randomized Factorial Design (CRFD) method that had two independent variables such as different dosages and temperatures was used. From five dosages (0 mg/L; 5 mg/L; 10 mg/L; 15 mg/L; 20 mg/L) and three temperature treatments (ambient temperature (about 25°C; 28°C; 32°C), it was found that the highest male percentage of primary sexuality (88.33%), secondary sexuality (85%), and highest total testosterone levels (TL) (1.986 ng/L) were at the treatments with the highest dosages and temperature, while for the highest survival rate were at almost in all B treatments (5 mg/L) and b levels (28°C), in which the survival rate was 100%. For all of these results above, the results were significant.